(untitled) (Journal of Hama University, 2025)
The extent to which fourth grade students possess analytical thinking skills in science "A field study in basic education schools in the city of Latakia" Summary The research aimed to determine the extent to which fourth-grade students possess analytical thinking skills in science. To achieve this, the descriptive approach was used, and a test for analytical thinking skills was prepared. Its validity and reliability were confirmed, and it included five skills. The test was distributed to a sample of fourth grade students, numbering (238) male and female students. The results of the research showed that the research sample possesses analytical thinking skills with an average rating, and there is no difference between males and females in the extent to which they possess analytical thinking skills. The research ended with a set of proposals, such as the need to pay attention to developing analytical thinking skills among basic education students when presenting them in the curricula. Keywords: analytical thinking skills, fourth grade students.